Investigating online incivility and its consequence on online discourse engagement - San Pascual, Maria Rosel Sanchez
Drawing from the main concepts of democracy, public discourse and incivility, the main conjectures of the Spiral of Silence (SOS) Theory, and the literature on public opinion effects and public discourse incivility, this dissertation investigates how online exposure to civil or uncivil expression of issue support or dissent consequently affects engagement or non-engagement in online public discourse. Data were generated from a fully-online and fully-offsite experiment which simulated an online reader comments environment. Findings reveal that the consequences of civility and incivility are more nuanced than what was initially predicted. In particular, findings uncover the paradoxes of civility and incivility. The paradox of civility shows that, while civility generally enables participation, civility may insufficiently disinhibit individuals from extending their participation in the ongoing discussion. Meanwhile, the paradox of incivility exposes that, while incivility may impede participation, it may also prod individuals to join the ongoing discussion. Furthermore, findings bare the spiral of civility, where civility begets more civility, and conversely, the spiral of incivility, where incivility engenders more incivility. Therefore, while findings show that, at the individual level, incivility may have its purpose in getting some people to speak online, at the societal level, civility and the civility that it further begets remain to be the ethical way of conducting oneself online because it follows the basic principle of respect and nonmaleficence. Ways and means to push for civility should then be aggressively explored and implemented so that civil expression becomes the norm in public discourse."